INFRASTRUCTURE PERFORMANCE ANALYSIS OF THE ON-SITE DOMESTIC WASTEWATER MANAGEMENT SYSTEM IN BANDA ACEH - Azna, Nauwalul Azka; Kamal, Nurul (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The On-Site Domestic Wastewater Management System (OWMS) serves as the primary sanitation service in Banda Aceh, playing a critical role in managing household wastewater. This study aims to analyze the existing conditions of OWMS infrastructure, evaluate the performance of its management, and formulate improvement strategies using a SWOT analysis. The research employed a descriptive approach with data collection conducted through field surveys, interviews, direct observations, and secondary data from relevant municipal agencies. Samples were selected purposively from septic tank users, faecal sludge transport operators, Faecal Sludge Treatment Plant (FSTP) personnel, and technical institutions. The findings indicate that the OWMS infrastructure faces several challenges across its subsystems, including household-level treatment, sludge transportation, and sludge processing. These challenges include low frequencies of scheduled desludging, limited vehicle availability, and insufficient public awareness regarding safe sanitation practices. Furthermore, the management evaluation highlights the need for regulatory strengthening, improved inter-agency coordination, and operational enhancements. The SWOT analysis produced several priority strategies, including capacity development, optimization of scheduled desludging services, institutional strengthening, and expanded sanitation education. This study provides foundational insights to improve on-site sanitation systems and support the achievement of safe sanitation services in Banda Aceh.